The material standard in the jurisprudence of the Administrative Court in Tunisia - Fadoua Moncef Elleuch (International Journal of Law Research and Studies, 2025)
The establishment of the material standard in the appeal for abuse of power has witnessed development at the legislative level. In the original text of the law of June 1, 1972 relating to the Administrative Court, the legislator adopted an organic standard to determine the jurisdiction of judge abuse power. However, the Administrative Court did not adhere to the organic standard and adopted a material standard to determine its jurisdiction. The 1996 revision aligned itself with the judicial jurisprudence of the Administrative Court and established a material standard for determining jurisdiction in the appeal for abuse of power. At the same time, Law No. 38 of 1996, dated June 3, 1996, assigned jurisdictional blocks to both the judicial judge and the administrative judge. The activation of the material standard has clearly appeared in disputes of public establishments, decisions related to the organization of the legislative authority, the organization of the judicial authority and decisions issued by bodies not specified by law.                        Regarding full litigation, both the Administrative Court and the Conflict of Jurisdiction Council prevailed over the material standard in public establishment disputes, and the judge did not abide by the bloc of jurisdiction that the legislator assigned to the judicial judge, whether with regard to the relationship between public establishments and their clients or with regard to disputes that arise between them and others. In addition, the Administrative Court prevailed over the material standard in lawsuits related to real estate, whether those related to seizure or those related to private property of the administration.                                                         The study reached results, the most important of which is the lack of consistency and harmony between the requirements of the law of June 1, 1972, as amended, and Law No. 38 of 1996 with regard to standards of jurisdiction and abandoning the technique of blocks of jurisdiction.
Keywords: Material Standard; Administrative Court; Jurisdiction Blocks; Conflict of Jurisdiction Council